2021
DOI: 10.1101/2021.08.13.456272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cooperative network at the nuclear envelope counteracts LINC-mediated forces during oogenesis in C. elegans

Abstract: Oogenesis involves meiosis and oocyte maturation. Both processes rely on mechanical forces (Lee et al., 2015; Nagamatsu et al., 2019; Rog and Dernburg, 2015; Sato et al., 2009; Tsatskis et al., 2020; Wynne et al., 2012), which can be transduced from the cytoskeleton to the nuclear envelope (NE) through linker of nucleoskeleton and cytoskeleton (LINC) complexes (Burke, 2018; Chang et al., 2015; Fan et al., 2020; Link et al., 2014). Gametes must protect their genomes from damage in this mechanically stressful en… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…4a). The abundance of MJL-1 detected on western blots was also strongly reduced following auxin-induced degradation of SUN-1 (Liu et al, 2021) (Fig. S2b).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…4a). The abundance of MJL-1 detected on western blots was also strongly reduced following auxin-induced degradation of SUN-1 (Liu et al, 2021) (Fig. S2b).…”
Section: Resultsmentioning
confidence: 97%
“…4a). The abundance of MJL-1 detected on western blots was also strongly reduced following auxin-induced degradation of SUN-1 (Liu et al, 2021). These findings indicate that SUN-1 is required for subcellular localization and/or stabilization of MJL-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in somatic cells showed phosphorylation’s role in regulating the flexibility of the lamina meshwork 62 . Targeted depletion of the lamina in C. elegans oocytes provokes nuclear collapse due to rigidity loss of the nucleus, which cannot resist the forces exerted by the cytoskeleton 78 . These results suggest that the lamina is needed to counteract the forces transmitted through the LINC complex.…”
Section: Discussionmentioning
confidence: 99%